Pengaruh Flexible Work Arrangement (FWA), Compensation, dan Career Development terhadap Job Satisfaction dan Pengaruhnya terhadap Turnover Intention dan Job Performance - Kurnia Indy Pratama S.; Justine Tanuwijaya (Jurnal Maksipreneur, 2023)
The development of competition in the digital era requires reliable human resources. In this digital era, human resources have an important part in helping an organization to chase organizational goals. However, it cannot be denied that organizational competition for human resources is a concern for an organization. This competition has an impact on the turnover intention of every employee in the organization. This study aimed to analyze the effect of FWA, compensation, and career development variables on job satisfaction as well as to analyze the effect of job satisfaction on job performance and turnover intention and the effect of job performance on turnover intention. The data processing method in this study used structural equation modeling (SEM). The results of the study indicate that career development has an effect on job satisfaction, FWA and compensation have no effect on job satisfaction, job satisfaction has an effect on job performance and turnover intention, and job performance has no effect on turnover intention.